2019
DOI: 10.1021/acs.jafc.9b02263
|View full text |Cite
|
Sign up to set email alerts
|

Role of Food Phytochemicals in the Modulation of Circadian Clocks

Abstract: The circadian clock is an intrinsic mechanism of biological adaptation to the cyclical changes of the environment. The circadian rhythm disorders affect the life activities of organisms. A variety of phytochemicals (e.g., polyphenols, flavonoids, alkaloids, and melatonin) reportedly can regulate the expression and rhythm of circadian clock genes and stabilize the internal environment. This perspective focuses on the relationship of circadian clock genes with oxidative stress, inflammatory response, and metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…People with continued circadian rhythm disruption have relatively high prevalence rate of hyperlipidemia, atherosclerosis, or other diseases (Bass & Takahashi, 2010). Studies have represented that TP can regulate the comparatively shallow diurnal vibration of gene expression in the biological clock of liver, which are caused by persistent darkness (Liu et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…People with continued circadian rhythm disruption have relatively high prevalence rate of hyperlipidemia, atherosclerosis, or other diseases (Bass & Takahashi, 2010). Studies have represented that TP can regulate the comparatively shallow diurnal vibration of gene expression in the biological clock of liver, which are caused by persistent darkness (Liu et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The circadian clock system of mammalian is hierarchically organized, contains a master clock situated in the suprachiasmatic nucleus of the hypothalamus. While the peripheral clock system is mainly distributed in heart, liver, intestine, adipose, and muscle tissues (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SDFs were extracted from wheat brans [21] and further treated by α-amylase and protease E (7892 and 1020 U mL -1 ; Novozymes Biotechnology Co., Ltd., Tianjin, China), and amyloglucosidase (1,176 U g -1 , Tianjin Noao Science & Technology Development Co., Ltd., Tianjin, China) for removing starch and protein according to a previous method. [22] The saccharide composition of the SDF fractions and their molecular weight and structural features were determined using colorimetric analysis, high performance liquid chromatography (HPLC), and gas chromatography (GC) profiling as described previously [23] and the results are presented in Table 1, Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidences indicated that phytochemicals, especially polyphenols, directly impact circadian rhythms of the entire body. [ 18 ] Resveratrol (RSV) can regulate circadian clock genes in fibroblast cells and concomitantly activate SIRT1, which mediates Bmal1 and Clock in a deacetylase‐dependent manner. [ 19–21 ] Knockout of CLOCK or BMAL1 induces insulin resistance in the liver of mice, which can be reversed by RSV.…”
Section: Introductionmentioning
confidence: 99%